A cross-reactive monoclonal antibody to nematode haemoglobin enhances protective immune responses to Nippostrongylus brasiliensis. - Natalie E Nieuwenhuizen; Jeanne M Meter; William G Horsnell; J Claire Hoving; Lizette Fick; Michael F Sharp; Matthew G Darby; Suraj P Parihar; Frank Brombacher; Andreas L Lopata (Public Library of Science (PLoS), 2013)
BACKGROUND: Nematode secreted haemoglobins have unusually high affinity for oxygen and possess nitric oxide deoxygenase, and catalase activity thought to be important in protection against host immune responses to infection. In this study, we generated a monoclonal antibody (48Eg) against haemoglobin of the nematode Anisakis pegreffii, and aimed to characterize cross-reactivity of 4E8g against haemoglobins of different nematodes and its potential to mediate protective immunity against a murine hookworm infection. METHODOLOGY/PRINCIPAL FINDINGS: Immunoprecipitation was used to isolate the 4E8g-binding antigen in Anisakis and Ascaris extracts, which were identified as haemoglobins by peptide mass fingerprinting and MS/MS. Immunological cross-reactivity was also demonstrated with haemoglobin of the rodent hookworm N. brasiliensis. Immunogenicity of nematode haemoglobin in mice and humans was tested by immunoblotting. Anisakis haemoglobin was recognized by IgG and IgE antibodies of Anisakis-infected mice, while Ascaris haemoglobin was recognized by IgG but not IgE antibodies in mouse and human sera. Sequencing of Anisakis haemoglobin revealed high similarity to haemoglobin of a related marine nematode, Psuedoterranova decipiens, which lacks the four -HKEE repeats of Ascaris haemoglobin important in octamer assembly. The localization of haemoglobin in the different parasites was examined by immunohistochemistry and associated with the excretory-secretary ducts in Anisakis, Ascaris and N. brasiliensis. Anisakis haemoglobin was strongly expressed in the L3 stage, unlike Ascaris haemoglobin, which is reportedly mainly expressed in adult worms. Passive immunization of mice with 4E8g prior to infection with N. brasiliensis enhanced protective Th2 immunity and led to a significant decrease in worm burdens. CONCLUSION: The monoclonal antibody 4E8g targets haemoglobin in broadly equivalent anatomical locations in parasitic nematodes and enhances host immunity to a hookworm infection.